Tetrapropylammonium Surfactants as Micellar Modifiers for Enhanced Oil Recovery Application - Tretya Ardyani; Azmi Mohamed; Suriani Abu Bakar (JURNAL SPEKTRA, 2019)
The article addresses an interesting yet unexplored issue in the development of surfactants for microemulsion stabilisation: the role of surfactant headgroup modification to tune the surfactant performances in CO2,water, and cyclohexane. The aqueous properties, and phase behaviour of novel tetrapropylammonum (TPA) surfactants is described. For comparison purposes, the related sodium surfactant (Na-AOT, Na-AOT4, and Na-TC14) are also used to form microemulsions. Observation on the surfactant aqueous properties revealed that the swapping into TPA does not significantly increases the effectiveness of the surfactant in lowering the surface air-water (a/w) tension. The introduction of bulky TPA counterions to normal sulfosuccinate surfactant generally leads to a transition from spherical micellar to extended sheet-like micellar aggregates in water. All in all, the results point minor effect on the headgroup structure modification towards the compatibility of surfactant with CO2.